The Content of Using Natıonal Values ın Spırıtual and Moral Educatıon of Children - Kuttibekova Guljan Tulepbaevna; Ibragimova Mahliyo Shuxrat Qizi (Genius Journals, 2023)
In this article, the use of national values in the spiritual and moral education of children in the family is considered one of the current problems in terms of prevention of educational problems that may arise in them. The problems that can be touched by the help of this topic in most cases have a social content, and they can be expressed as follows.
Keywords: spiritual-ethical; family; honor; value